Modelling and fabricating subsonic wing - Khairul Amin, Othman (University Malaysia Sarawak, UNIMAS., 2005)
Aerodynamics is the study of forces and the resulting motion of objects through the fluid. Aerodynamics affects the motion of a large airliner, a model rocket or a kite flying high overhead. The purpose of this study is to determine the best subsonic wing profile.